Suppressing voltage spikes of MOSFET in H‐Bridge inverter circuit - Aboadla, Ezzidin Hassan Elmabrouk; Khan, Sheroz; Abdul Kadir, Kushsairy; Yusof, Zulhairi Md; Habaebi, Mohamed Hadi; Habib, Shabana; Islam, Muhammad; Hasan, Mohammad Kamarul; Hossain, Eklas (MDPI, 2021)
Power electronics devices are made from semiconductor switches such as thyristors, MOSFETs, and diodes, along with passive elements of inductors, capacitors, and resistors, and integrated circuits. They are heavily used in power processing for applications in computing, communication, medical electronics, appliance control, and as converters in high power DC and AC transmission in what is now called harmonized AC/DC networks. A converterʹs operation is described as a periodic sequencing of different modes of operation corresponding to different topologies interfaced to filters made of passive elements. The performance of converters has improved considerably using high switching frequency, which leads to a significant improvement in a power converterʹs performance. However, the high dv/dt through a fast‐switching transient of the MOSFET is associated with parasitic components generating oscillations and voltage spikes having adverse effects on the operation of complementary switches, thereby affecting the safe operation of the power devices. In this paper, the MOSFET gate‐driver circuit performance is improved to suppress the H‐Bridge inverter ʹs voltage spikes. The proposed technique is a simple improvement to the gate driver based on the IR2112 driver (IC) by adding a capacitor to attenuate the effect of parasitic components and the freewheeling current, suppressing the negative voltage spikes. This paper’s main contribution is to improve the gate driver circuitʹs capability for suppressing the voltage spikes in the H‐Bridge inverter. The improved gate driver circuit is validated experimentally and is compared with the conventional gate driver. The experimental results show that the proposed technique can effectively suppress the MOSFET’s voltage spikes and oscillations.